2021
DOI: 10.3390/app112411684
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stacked Ensemble for Hate Speech Recognition

Abstract: Detecting harmful content or hate speech on social media is a significant challenge due to the high throughput and large volume of content production on these platforms. Identifying hate speech in a timely manner is crucial in preventing its dissemination. We propose a novel stacked ensemble approach for detecting hate speech in English tweets. The proposed architecture employs an ensemble of three classifiers, namely support vector machine (SVM), logistic regression (LR), and XGBoost classifier (XGB), trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Many proposed works performed hate speech detection as a binary classification problem and considered a broad concept such as detecting bullying and derogatory language. In [23], the authors presented an original technique to detect hatred speech in English tweets. For that, they utilized three models, i.e., logistic regression (LR), XGBoost classifier (XGB), and support vector machine (SVM).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Many proposed works performed hate speech detection as a binary classification problem and considered a broad concept such as detecting bullying and derogatory language. In [23], the authors presented an original technique to detect hatred speech in English tweets. For that, they utilized three models, i.e., logistic regression (LR), XGBoost classifier (XGB), and support vector machine (SVM).…”
Section: Related Workmentioning
confidence: 99%
“…K-NN algorithm does not make any hypothesis on underlying data. Thus, it is a non-parametric algorithm [23]. KNN is a lazy learner algorithm because it holds the dataset and it achieves an activity on the dataset at classification, i.e., does not memorize from the training set immediately.…”
Section: ) K-nearest Neighbor (K-nn)mentioning
confidence: 99%
See 2 more Smart Citations
“…Kokatnoor et al [15] A model called Stacked Weighted Ensemble is suggested for the identification of hate speech. Along with certain separate classifiers.…”
Section: Introductionmentioning
confidence: 99%